(untitled) (Scientific journal of the Fergana State University, 2026)
In the article, the proposal of the President of Uzbekistan Shavkat Miromonovich Mirziyoyev to the participants of the 72nd session of the UN to adopt a special resolution on a global scale called "Enlightenment and religious tolerance" is to "end ignorance, establish tolerance and mutual respect, ensure freedom of religion" and based on the fact that it is aimed at protecting their rights and help prevent their discrimination, taking into account the fact that such a principle, which is considered the most important in Sufism, is aimed at the daily life of people. As a result of the study, Sufism was identified, expressed by the moderate Sufism of Abu Hamid al-Ghazali and the philosophical and mystical views of Muhiddin ibn al-Arabi on being as “wahdat ul-wujud”.Both directions of Sufi theory served to harmonize Sufi practice with reason. Famous Sufi theorists such as Imam al-Ghazali and Ibn al-Arabi rationalized the Sufi worldview and gave it the status of a “theoretical science” that has the property of “communication with the deity” as a unique knowledge of Sufi experience. The article reveals the ideas of peace and tolerance of these two great scientists, the significance of their mystical and philosophical heritage today.